أخطاء الترجمة من اللغة الإنجليزية إلى العربية دراسة تحليلية لكتاب (نموذج المستعمِر للعالَم) المترجم لبلاوت أنموذجا /أعداد، محمد برهان عبد الحميد - عبد الحميد، محمد برهان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research aims to investigate translation from English to Arabic in the Arab world, and the quality of translated books produced by translation centers and institutions. Despite the lack of works translated to Arabic in the Arab world - compared to the developed countries -, some of these works have translation quality issues which have led to loss of confidence in them. Among these works is “The Colonizer's Model of the World Geographical Diffusionism and Eurocentric History'' by James Morris Blaut, in which the researcher tries to compare the original English text with its Arabic translation. This is followed by an analytical study of translation, linguistic and technical errors that are found in the Arabic version, which affected the coherence and intellectual sequence of the sentences and paragraphs of the book. Although the book has been subjected to reviewing, linguistic correction, technical supervision, and was printed by the well-known National Center for Translation and Publishing in Cairo there are still errors in many aspect found in the translation. The researcher deals with these errors on three linguistic levels (lexical, syntactic and semantic), and in three linguistic sections (vocabularies, compositions and methods), in accordance to the translation quality standards. The Arabic language criteria for correct and usages was also used. Among the significant conclusions of the study are the errors which were committed by the translators were not complicated and profession-related errors. It also appears that the translator did not commit to a constant translation strategy in which one word/terminology is translated to two different meanings, one of them can simply be inaccurate. Ironically, some of these errors occur several times in one page. The current study is able to prove that this translation effort contains many errors which have hurt the quality of the translation despite the submission of this translation to a number of specialists, and published at a well know center in the Arab world.